The John F. Sonnett Memorial Lectures at Fordham University School of Law : a half-century of advocacy and judicial perspectives - Kenny, Dennis J.; Davidson, Joel E. (Fordham University Press, 2018)
The John F. Sonnett Memorial Lectures explore the evolution of legal ethics, legal training, prisoner rights, the role of the judiciary and other jurisprudential issues. The lectures continue to impact the current debates and discussions surrounding these issues.